Operation of a Prototype CTBT Infrasound Array in Arctic Alaska - Olson, John V.; Wilson, Charles R. (2000)
A prototype Comprehensive Nuclear-Test-Ban-Treaty (CTBT) infrasound array was established in Fairbanks, Alaska in a wooded area on the campus of the University of Alaska in December 1999. The implementation of the array was carried out as part of the second phase of our studies of natural infrasound in arctic regions. In our implementation of the array four microphones were placed in the form of a triangle with one microphone placed near the center. During the winter months we also continued to monitor the response of three colocated microphones attached to different noise reducers to follow the relative effectiveness of the noise reducers in arctic conditions. These conditions ranged from severe winter cold with deep snow pack to the mild days of summer. During the period of operation we detected several examples of naturally occurring infrasound as well as many man-made sounds. The naturally occurring infrasound signals of greatest interest are the 2-5 second period waves produced by marine storms that are termed microbaroms. We are studying these signals in order to estimate their spatial coherence. We believe that they can be identified and eliminated as a contaminating signal for CTBT arrays worldwide based upon their coherence properties. Other natural signals received included auroral infrasound, mountain-associated waves, thunder from summer storms and the eruption of the Japanese volcano, Mount Usu on March 31, 2000. A bolide that passed over central Alaska and exploded over Whitehorse, Canada on January 18, 2000 produced no detectable signal in our array. Man-made signals detected on our array are plentiful and varied. We witness every jet aircraft departure from the international airport located several miles away. Also recorded were the reports of military howitzers at the local army base as well as firework displays during holiday celebrations. Published in Proceedings of the Annual DoD/DOE Seismic Research Symposium: Planning for Verification of and Compliance with the Comprehensive Nuclear-Test-Ban Treaty (CTBT) (22nd), held in New Orleans, LA on 13-15 Sep 2000. U.S. Government or Federal Rights. The original document contains color images.